Ideal Formulation of Diversion in the Indonesian Child Criminal System - Dewi, Erna (Budapest International Research and Critics University, 2022)
The settlement of cases of children in conflict with the law in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System has undergone changes in fundamentals. The change lies in the adoption of the concept of diversion in the settlement of children's cases. However, diversion is not fully in favor of all Indonesian children. The existence of categorization in the application of diversion in Article 7 paragraph (2) creates discriminatory treatment for children in conflict with the law and is inconsistent with the provisions of Article 2 letter c of Law Number 11 of 2012. The issues to be discussed are related to the legal politics of determining diversion in the Act. Law Number 11 of 2012, the current implementation of diversion, and the formulation of diversion in Law Number 11 of 2012. The research method uses a normative juridical approach. Based on the discussion, it is concluded that diversion is the will of the community. Currently, mandatory diversion is applied at every level of examination of child cases. However, the categorization of diversion in Article 7 paragraph (2) is still discriminatory, therefore the current application of diversion is not fully in favor of the best interests of the child. The ideal formulation of diversion includes (1) mandatory diversion for every criminal act committed by a child because the child who commits a crime is influenced by external factors or not purely his will. (2) Punishment of a child must prioritize the best interests of the child. (3) punishment of children that prioritizes rehabilitation, education, and resocialization.